Fractal Dimension Analysis And Fractal Properties of Financial Markets - Jedličková, Marie (Vysoké učení technické v Brně,Fakulta podnikatelská, 2016)
Financial markets are a subject of many studies and research purposes. The ability to correctly observe and describe the dynamics of financial markets would mean the possibility to predict its future behaviour. Many approaches and methods have been used to achieve this objective. In recent history it has come to light that many natural phenomena could be described using fractal geometry. Alongside with the fractals can be often found the application of fuzzy logic and also the theory of chaos. These three concepts are recently very powerful in describing complex system and getting closer to understanding them. This paper deals with the basic concepts of fractal analysis and also fuzzy logic and the possibility to use those to observe financial markets and analyze their behaviour. The purpose of this is to present the reader with introduction to the problematics and propose starting concepts to begin the research into the matter.
Keywords: fractal; financial markets; fractal dimensions; fuzzy set; Mandelbrot; market prediction